Composite structures for civil and architectural engineering - Kim, D.-H. (Duk-Hyun). (London ; New York : E & FN Spon, 1995)
Introduction; Properties of composites; Classical theory of elasticity and mechanics; Eigenvalue problems of beams and frames of isotropic materials; Anisotropic; One-dimensional structural elements of composite materials; Plates and panels of composite materials; Failure of composites; Joints; Design.
Includes bibliographical references and indexes.
Keywords: Composite construction; Composite construction; Composite materials -- Mechanical properties; Structural analysis (Engineering).; Structures -- Composite materials